2012
DOI: 10.1104/pp.111.191494
|View full text |Cite
|
Sign up to set email alerts
|

TherolBGene Suppresses Reactive Oxygen Species in Transformed Plant Cells through the Sustained Activation of Antioxidant Defense      

Abstract: The rolB (for rooting locus of Agrobacterium rhizogenes) oncogene has previously been identified as a key player in the formation of hairy roots during the plant-A. rhizogenes interaction. In this study, using single-cell assays based on confocal microscopy, we demonstrated reduced levels of reactive oxygen species (ROS) in rolB-expressing Rubia cordifolia, Panax ginseng, and Arabidopsis (Arabidopsis thaliana) cells. The expression of rolB was sufficient to inhibit excessive elevations of ROS induced by paraqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 54 publications
7
62
0
1
Order By: Relevance
“…The control (non-transformed) cell line R was transformed with the rolB gene to generate cell lines RBM and RBH with different level of the target gene expression. 5 The strength of expression of rolB in the RBM culture is similar to the expression of rolB from its own 5' promoter. 7 In the RBH culture, rolB has a 2.5-fold higher expression level than in the RBM culture.…”
Section: Can Plant Oncogenes Inhibit Programmed Cell Death?mentioning
confidence: 76%
See 3 more Smart Citations
“…The control (non-transformed) cell line R was transformed with the rolB gene to generate cell lines RBM and RBH with different level of the target gene expression. 5 The strength of expression of rolB in the RBM culture is similar to the expression of rolB from its own 5' promoter. 7 In the RBH culture, rolB has a 2.5-fold higher expression level than in the RBM culture.…”
Section: Can Plant Oncogenes Inhibit Programmed Cell Death?mentioning
confidence: 76%
“…It was previously shown that the majority of antioxidant genes studied, including those encoding the Cu/Zn superoxide dismutases, catalases, ascorbate peroxidases and class III peroxidase genes, were coordinately upregulated in rolB-expressing cells. 5,19 RolB permanently sustains an active anti-oxidative environment in transformed cells and simultaneously maintains their normal redox balance, providing physiological conditions for adaptation to external oxidative stress. 5 While the cellular conditions leading to PCD induction are linked with an imbalance in redox status, 20 this function of RolB may be important for PCD prevention.…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations
“…They consist in non-fluorescent molecules that become fluorescent when oxidised by ROS, and the emitted fluorescence can be observed by fluorimetry and/or by fluorescent microscopy, an advantage of such probes (Benikhlef et al, 2013;Bulgakov et al, 2012;Fester and Hause, 2005;Guo et al, 2010;Kolla et al, 2007;L'Haridon et al, 2011;Li et al, 2007;Liu et al, 2010;Ma et al, 2013;Peleg-Grossman et al, 2012;Plancot et al, 2013;Tada et al, 2004;Wen et al, 2008;Ye et al, 2013). Luminol or luminol analogues are sensitive chemiluminescent probes used to quantify a relative intensity of ROS by counting the emitted light with a luminometer, CDD camera or a scintillation counter (Dubreuil-Maurizi et al, 2010;Flury et al, 2013;Kunz et al, 2006;L'Haridon et al, 2011;Mersmann et al, 2010).…”
Section: Detection Of Rosmentioning
confidence: 99%